Predictive Analysis in Islamic Accounting: Understanding Financial Trends Through Advanced Technology - Oktaviani, Wulan; Safira, Dinda; Naja, Nailun; Meilani, Ananda; Wulan Oktaviani; Dinda Safira; Nailun Naja; Ananda Meilani (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2024)
This research aims to map studies related to technology applied in Islamic accounting using the bibliometric method of VOSviewer and a literature review to examine and analyze the application of advanced technology in understanding and predicting financial trends in the Islamic accounting sector. This study employs a mixed-method research approach, utilizing quantitative methods for the bibliometric study and qualitative methods for the literature review. The results indicate that, based on data collected from 2010 to 2024, there are 601 Scopus journals related to Islamic accounting technology. The visualization results from the VOSviewer software regarding the research map related to big data, blockchain, artificial intelligence, and sharia accounting show the presence of 8 clusters with 141 topic items. This research demonstrates that the development of AI, blockchain, and big data in the Islamic accounting sector plays a significant role. The implications of this study suggest that advanced technology can enhance operational efficiency, identify risks, understand customer preferences in accordance with Islamic values, and emphasize the importance of developing employee skills in the Islamic accounting sector to operate technologies such as AI, blockchain, and big data